In utero and lactational exposure to fipronil in female rats: Pregnancy outcomes and sexual development - De Barros, Aline Lima [UNESP]; Rosa, Josiane Lima [UNESP]; Cavariani, Marília Martins [UNESP]; Borges, Cibele Santos [UNESP]; Villelae Silva, Patrícia [UNESP]; Bae, Julie Heejoo [UNESP]; Anselmo-Franci, Janete Aparecida; Cristina Arena, Arielle [UNESP] (Taylor & Francis, 2016)
Fipronil, a phenylpyrazole insecticide, is used in agriculture, veterinary medicine, and public health. Because this insecticide is considered a potential endocrine disruptor, the aim of this study was to examine the influence of perinatal exposure to fipronil on neonatal female reproductive system development. Pregnant rats were exposed (via gavage) daily to fipronil (0.03, 0.3, or 3 mg/kg) from gestational day 15 to day 7 after birth, and effects on the reproductive functions assessed on postnatal day (PND) 22. No signs of maternal toxicity were observed during daily treatment with fipronil. Perinatal exposure to the highest dose of fipronil (3 mg/kg) delayed the age of vaginal opening (VO) and first estrus without markedly affecting the anogenital distance (AGD). Further, exposure to 0.3 mg/kg fipronil produced a significantly shorter estrus cycle and reduced number of cycles during the period of evaluation. However, the other reproductive parameters analyzed, including fertility, hormone levels, sexual behavior, and histology of ovaries and uterus, displayed no marked alterations. In this experimental model, fipronil interfered with development of neonatal female reproductive system as evidenced by delay in VO and estrus cycle alterations without apparent significant effects on fertility. Further studies are needed to identify the mechanisms of action associated with the observed female reproductive system changes.